(untitled) (Research, Society and Development, 2021)
The objective of this study is to analyze the relationship between the dividend policy, based on two of its main measures - dividend yield and payout - and the volatility of the share price (VPA) in the Brazilian market in the period from 2010 to 2018: the final sample consisted of 357 companies listed on B3 (Brazil, Bolsa and Balcão). Two multiple linear regression models were used as methodology, with effects fixed and estimated by panel data. The results showed that the main variables of the dividend policy negatively influence the VPA, that is, given a reduction in the dividend yield or payment of dividends, there is an increase in the volatility of the share price of Brazilian companies. In addition, leverage has a positive relationship with VPA, while market value and company size have a negative relationship with the dependent variable. Profit volatility, however, was not statistically significant. The research contributes to the literature by exploring a topic that still has no consensus on the national scene, and has practical implications for investors and managers, as information on dividend yield and dividend payment can help them to analyze and execute more accurate strategies on the company’s financial analysis and investment decision-making.